Critical Discourse Analysis of the Song "im a girl like you" on Barbie Movies : Princess and the Pauper - Nur Luluk Maghfiroh; Yufa Valentina A; Rike Rachmadina P; Fatimah (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2025)
This study uses Teun A. van Dijk’s Critical Discourse Analysis to examine the song “I’m Just Like You” from Barbie: The Princess and the Pauper. It analyzes how language in the song reflects social ideologies, constructs identity, and engages with gender and class power relations. Through Van Dijk’s model—text, cognition, and social context—the study finds that the lyrics promote emotional equality and shared identity between two female characters of different social classes. Linguistic features such as affixation, lexical choice, and symmetrical dialogue emphasize friendship, self-acceptance, and empowerment, though the critique of systemic inequality remains symbolic. The study concludes that Barbie films socialize young audiences into ideas of femininity and equality within commercially acceptable limits, highlighting the role of media language in shaping perceptions of gender and class.